Understand, Desing, Act: Climate-proof your supply chain - Selengia, Katherine; Sloan, Kealy; Glowka, Caroline; Lundy, Mark M.; Knueppel, Danielle; Teague, Elizabeth; Jassogne, Laurence T.P.; Giovannucci, Daniele; Ruíz, Pablo; Watene, George; Semroc, Bambi; Firl, Monica; et al. (2018)
Presentations of Understand, Desing, Act: Climate-proof your supply chain Module 1: Understand climate change Module 2: How is climate change affecting my supply chain Module 3: How can I manage the effects climate change in having on my supply chain? Module 4: How can I scale up climate smart agriculture? Module 5: How do I know my investment in climate smart agriculture is working? Module 6: How can I convince my company and others to work on CSA?